ANALYSIS OF THE LEGAL RELATIONSHIP BETWEEN PROSPECTIVE UMRAH PILGRIMS AND UMRAH TRAVEL IN LANGSA CITY - Dayyan, Muhammad; Ari, Teuku; Muzakkir (Institut Agama Islam Negeri Metro, 2024)
The Umrah Travel Business Practice in Indonesia is increasingly developing, promoted by distributing brochures, banners, billboards, and meetings with religious figures to invite the public to become prospective pilgrims. This study aims to analyze the Umrah travel business practice in Langsa City and analyze how the relationship between the travel party and prospective Umrah pilgrims and how the legal impact is. This study contributes to educating the public to avoid fraud and legal protection efforts for prospective Umrah pilgrims. This study was conducted with a qualitative approach that collected data through interviews with the travel party, the Ministry of Religion of Langsa City and Umrah pilgrims, both those who have performed Umrah and those who have not. Secondary data in the form of primary legal materials, government regulations and fatwas related to the Umrah travel business. The results of the study show that the legal relationship between Travel and prospective Umrah pilgrims in Langsa City is formed through down payment or settlement of Umrah costs offered by the travel agency. The legal relationship between the Umrah Travel Organizer and prospective pilgrims is still weak because there is no written agreement. The implications of this legal relationship have the potential for criminal acts if the Umrah Travel Agency intentionally causes the failure of departure, abandonment or failure of the return of Umrah Pilgrims, as regulated in Law Number 8 of 2019 concerning the implementation of the Umrah pilgrimage.